Morphological characteristics and biodiversity of mudskipper fish (Periophthalmus: Gobiidae) in mangrove ecosystem of coastal Bay of Tomini, Boalemo, Gorontalo Province, Indonesia - Dewi Wahyuni K. Baderan; Regina Valentine Aydalina; Marini Susanti Hamidun (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Baderan DWK, Aydalina RV, Hamidun MS. 2023. Morphological characteristics and biodiversity of mudskipper fish (Periophthalmus: Gobiidae) in mangrove ecosystem of coastal Bay of Tomini, Gorontalo Province, Indonesia. Biodiversitas 24: 498-507. The southern sea area of Gorontalo Province is part of Tomini bay, the biggest bay in Indonesia. This area has a unique biodiversity and is Sulawesi endemic. The mangrove forest in the coastal bay of Tomini Boalemo is one of the habitats for flora and fauna, a place for spawning, nurturing, and food hunting for fish. The mudskipper is a fish that lives in the mangrove area. This study aims to reveal the morphological characteristics and biodiversity of mudskipper (Periophthalmus: Gobiidae) in the ecosystem of Tomini Boalemo coastal bay of Gorontalo Province. This study employed a quantitative descriptive that also implemented purposive sampling as the sampling method in three ecosystem stations of Tomini Boalemo coastal bay (Dulupi, Bajo, and East Pentadu mangrove). The mudskippers were collected manually when the water was receding using a fish net. The sample which had been collected were then identified based on 22 morphological, 24 morphometric, and seven meristic characteristics. The identification results were then compared with the identification key. The mudskippers' species were then analyzed to determine the species' biodiversity (diversity, evenness, species richness, and dominance indexes). The research result revealed five species from Periophthalmus Genus: Periophthalmus argentilineatus, Periophthalmus kalolo, Periophthalmus malaccensis, Periophthalmus minutus, Periophthalmus variabilis, with total individuals 561. The score of H?: 1.09 showed that the diversity of mudskipper fish was categorized as medium. The evenness index was 0.99 obtained from 3 observation stations, while the lowest dominance index was on station II with a score of 0.34, and the score of R1 in each station was respectively (0.19); (0.36); and (0.2). The results of this study could be used as a database for the sustainable management of Tomini Bay to tackle the threats of species extinction through aquatic life protection and preservation to arrange the natural balance and support the availability of the coastal resource for future generations.